If

**a**and

**b**are equal positive integers then:

1)

**a = b**

*(given)*

2)

**a**

^{2}= ab*(multiply both sides by a)*

3)

**a**

^{2}- b^{2}= ab - b^{2}*(subtract b*

^{2}from both sides)4)

**(a + b)(a - b) = b(a - b)**

*(factor both sides)*

5)

**a + b = b**

*(divide both sides by a - b)*

6)

**2b = b**

*(replace a by b since a = b and simplify from b + b to 2b)*

7)

**2 = 1**

*(divide both sides by b)*

EDIT: Most folks were right. I'll find something more difficult for next time ;)

## Error

Your reply will be screened

Your IP address will be recorded